EFL STUDENTS' PERSPECTIVES ON INTEGRATING DUOLINGO INTO ORAL COMMUNICATION ACTIVITIES - Pipit Rahayu; Eripuddin Eripuddin; Azi Nurazima Juhastri; Muhammad Arif Murtopo; Ouafa Ouarniki (English Study Program University of Pasir Pengaraian, 2026)
English speaking skills play a vital role in education and professional settings, yet many university students, especially beginners, face challenges in developing fluency and confidence. The integration of technology and artificial intelligence has become an alternative solution to support speaking practice, with Duolingo emerging as a widely used platform. However, most previous studies focused on different applications or advanced learners, leaving a gap in understanding how beginner-level students perceive Duolingo in speaking activities. This study aims to explore the perceptions of second-semester students in the English Study Program at Universitas Pasir Pengaraian toward the use of Duolingo as a supplementary tool in speaking learning. Employing a qualitative descriptive method, data were collected from 22 participants through questionnaires and interviews to capture their experiences and opinions. The findings reveal that students generally have positive perceptions, highlighting Duolingo’s interactive features, gamification, instant feedback, and mobile accessibility, which motivate consistent practice and vocabulary development. Nevertheless, some limitations were identified, such as insufficient natural conversation, pronunciation accuracy, and cultural context. In conclusion, while Duolingo cannot fully replace authentic communication, it is perceived as a valuable complementary tool that enhances engagement and supports speaking skill development when integrated with classroom learning and real-life interaction.